Muck-based magnesium phosphate salt geopolymer as well as firing-free preparation method and application thereof
By combining shield muck with dihydrogen phosphate and dead-burned magnesium oxide, a muck-based magnesium phosphate geopolymer is prepared using a no-burning preparation method, which solves the problem of difficult shield muck treatment and high production cost of magnesium phosphate cement. problem, achieving the effects of efficient resource utilization and low-carbon energy saving.
Patent Information
- Application Number
- CN202411455828.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
There are difficulties in efficient resource utilization and treatment of shield slag. Traditional treatment methods occupy land, pollute the environment, and high-temperature calcination energy consumption limits the widespread application of slag in building materials.
By using shield muck as one of the raw materials, combined with dihydrogen phosphate and dead-burned magnesium oxide, a muck-based magnesium phosphate geopolymer is prepared using a no-burning preparation method to achieve effective resource utilization of muck and avoid high temperature Calcination treatment.
It realizes the efficient resource utilization of shield muck, reduces energy consumption, improves the early strength of muck-based magnesium phosphate geopolymer, meets the requirements of energy saving and low carbon, and solves the problem of high production cost and high cost of magnesium phosphate cement. Problems such as fast condensation speed.
Smart Images

Figure CN119306465A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a slag-based magnesium phosphate geopolymer and a firing-free preparation method and application thereof. Background Art
[0002] Magnesium phosphate cement (MPC) is a chemically bonded ceramic formed by acid-base neutralization reaction of dead-burned magnesium oxide and phosphate (such as ammonium dihydrogen phosphate, potassium dihydrogen phosphate, etc.). It is a new type of inorganic cementitious material. It has the characteristics of fast setting and hardening (even in negative temperature environment), high early strength, small shrinkage, high bonding strength, salt corrosion resistance, and the ability to solidify / stabilize heavy metals. It has received widespread attention in applications such as structural repair and reinforcement, protective coatings, and solidification of hazardous waste. However, magnesium phosphate cement also has some application limitations, mainly including high raw material costs, fast setting speed so that the construction operation time is limited, and large and concentrated heat release. Therefore, effectively solving the above problems is conducive to expanding the application scope of magnesium phosphate cement and enabling it to better play its irreplaceable advantages in specific fields.
[0003] With the rapid development of urban underground space development, shield method has been widely used. At the same time, the slag generated during shield construction has increased sharply year by year, and "slag siege" has become a pain point in the development of many cities. At present, shield slag is mainly treated by traditional methods of open-air stacking or simple landfilling. This method has problems such as occupying land, polluting soil and water bodies, destroying the city appearance, and affecting safety. The resource utilization rate of shield slag is less than 5%, and the problem of efficient resource utilization of shield slag needs to be solved urgently. Shield slag contains a large amount of silicon oxide and aluminum oxide, and has the potential to generate hydraulic hydration products, that is, it has potential use as a raw material for building materials. Shield slag is generally used in building materials. It needs to be calcined at high temperature first. This process consumes a lot of energy and emits a lot of carbon dioxide. It does not meet the requirements of energy saving and low carbon, and its wide promotion is obviously limited. Existing methods for resource utilization of unburned shield slag, such as preparing unburned bricks, require pressing and molding, and some even require autoclaving and high-temperature curing, and the prepared geopolymer has the problem of low early strength. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a slag-based magnesium phosphate geopolymer and a method and application thereof for preparing the slag-based magnesium phosphate geopolymer without firing. The present invention uses shield slag as one of the raw materials to prepare the slag-based magnesium phosphate geopolymer, thereby realizing the effective resource utilization of shield slag. The method provided by the present invention does not require pressing, high-temperature and high-pressure curing, and high-temperature calcination treatment, has low energy consumption, and the obtained slag-based magnesium phosphate geopolymer has high early strength.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a slag-based magnesium phosphate geopolymer without burning, comprising the following steps:
[0007] The geopolymer slurry is poured and vibrated to obtain a molded test block; the geopolymer slurry comprises, by weight, 10 to 50 parts of shield slag powder, 20 to 40 parts of dihydrogen phosphate, 40 to 90 parts of dead-burned magnesium oxide, 10 to 30 parts of water, 0 to 15 parts of borax, and 0 to 5 parts of an acid admixture;
[0008] The molded test blocks are hardened and cured in sequence to obtain a slag-based magnesium phosphate geopolymer; the hardening and curing temperatures are independently 20-25°C.
[0009] Preferably, the particle sizes of the shield slag powder and the dead-burned magnesium oxide are independently ≥40 meshes.
[0010] Preferably, the dihydrogen phosphate comprises potassium dihydrogen phosphate and / or ammonium dihydrogen phosphate;
[0011] The particle size of the dihydrogen phosphate is ≥100 mesh.
[0012] Preferably, the particle size of the dead-burned magnesium oxide is ≥40 mesh.
[0013] Preferably, the acid additive includes at least one of acetic acid, citric acid and oxalic acid.
[0014] Preferably, the method for preparing the geopolymer slurry comprises the following steps: dry-mixing shield slag powder, dihydrogen phosphate, dead-burned magnesium oxide and borax, and sequentially slowly and rapidly mixing the dry-mixed powder with an acid admixture and water to obtain the geopolymer slurry;
[0015] The dry mixing time is 1 to 3 minutes;
[0016] The slow stirring speed is 135-145 r / min, and the time is 30-60 s;
[0017] The rapid stirring speed is 275-295 r / min, and the time is 2-5 min.
[0018] Preferably, the vibration molding time is 1 to 3 minutes.
[0019] Preferably, the ambient humidity of the hardening and curing is independently 50-95%; the hardening time is 1-6 hours;
[0020] The total time of hardening and curing is 1 to 28 days.
[0021] The present invention provides a slag-based magnesium phosphate geopolymer prepared by the firing-free preparation method described in the above technical scheme.
[0022] The present invention also provides the use of the slag-based magnesium phosphate geopolymer described in the above technical solution as a building material.
[0023] The present invention adds shield slag as part of the raw material to the production process of magnesium phosphate cement prepared from dihydrogen phosphate and dead burned magnesium oxide, and utilizes the unique advantages of huge early heat release of magnesium phosphate cement and phosphate protonation effect, solves the problems of low utilization rate of shield slag, low processing efficiency, low strength, etc., and meets the requirements of energy saving and low carbon, and the early strength of the prepared slag-based magnesium phosphate geopolymer is high. At the same time, the shield slag contains a large amount of silicon oxide and aluminum oxide, has the potential to generate hydraulic hydration products, can replace part of the raw materials of magnesium phosphate cement, reduce the production cost of magnesium phosphate cement, improve its economic benefits, solve the problems of high production cost, fast setting speed, certain restrictions on construction operation time, large and concentrated heat release, and realize the setting and heat release of magnesium phosphate cement. The present invention combines shield slag and magnesium phosphate cement, and provides a new method for magnesium phosphate cement to stimulate and solidify unburned shield slag, which can effectively improve the resource utilization efficiency of shield slag, reduce environmental pollution, promote the sustainable development of the field of building materials, and bring considerable economic benefits.
[0024] The slag-based magnesium phosphate geopolymer prepared by the present invention combines the characteristics of rapid hardening, early high strength, and heavy metal solidification of magnesium phosphate cement, improves the processing efficiency and environmental safety of shield slag, and can prepare slag-based magnesium phosphate geopolymer with excellent performance after short-term maintenance (e.g., 1d), achieving the goal of efficient processing of slag and preparing high-performance building materials. The slag-based magnesium phosphate geopolymer prepared by the present invention has shield slag in its raw materials without high-temperature calcination treatment, and magnesium phosphate cement is also widely regarded as a new type of green building material, which meets the requirements of energy saving and low carbon when slag resources are utilized. The slag-based magnesium phosphate geopolymer prepared by the present invention reduces the dependence on traditional raw materials and reduces the production cost of magnesium phosphate cement by using shield slag as part of the raw material. The slag-based magnesium phosphate geopolymer prepared by the present invention can control the setting time of the material by controlling the ratio of magnesium phosphate cement and shield slag, improve construction efficiency, and improve the heat release of the material to a certain extent.
[0025] The slag-based magnesium phosphate geopolymer prepared by the present invention has components containing active silicon and active aluminum in the shield slag in the raw materials being excited, participating in the acid-base reaction of magnesium phosphate cement, exerting the potential ability to generate hydraulic hydration products, and being beneficial to improving the comprehensive performance of the slag-based magnesium phosphate geopolymer. The slag-based magnesium phosphate geopolymer prepared by the present invention has shield slag in the raw materials providing a large number of nucleation sites for the crystallization of hydration products in the system, promoting the orderly growth of crystals, and being beneficial to improving the comprehensive performance of the slag-based magnesium phosphate geopolymer. The slag-based magnesium phosphate geopolymer prepared by the present invention has unreacted shield slag and reacted shield slag in the raw materials both reducing the total porosity of the system, making the system structure more compact, and being beneficial to improving the comprehensive performance of the slag-based magnesium phosphate geopolymer. The slag-based magnesium phosphate geopolymer prepared by the present invention has shield slag in its raw materials, which reduces the alkalinity of the system, reduces the maximum heat release rate of the system and prolongs the time for the peak to arrive, which can effectively improve the heat release of the system. At the same time, the heat release of the system increases the energy of the active component molecules in the shield slag, so that more molecules can reach the activation energy, thereby accelerating the reaction rate, which is beneficial to improving the comprehensive performance of the slag-based magnesium phosphate geopolymer. The slag-based magnesium phosphate geopolymer prepared by the present invention can effectively realize the solidification / stabilization of heavy metals that may be contained in the shield slag in its raw materials through synergistic effects such as chemical bonding, adsorption, and physical encapsulation, and convert the shield slag containing heavy metals into environmentally friendly building materials, reduce environmental pollution, and is beneficial to achieving the environmental safety of the slag-based magnesium phosphate geopolymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the phase composition diagram of the slag-based magnesium phosphate geopolymer TIMA prepared in Example 8;
[0027] Figure 2 Element distribution diagram of the slag-based magnesium phosphate geopolymer prepared in Example 8 (BSE background);
[0028] Figure 3 This is an enlarged view of the phase region of the slag-based magnesium phosphate geopolymer prepared in Example 8;
[0029] Figure 4 The EDS energy spectrum and element quantitative statistical diagram of the slag-based magnesium phosphate geopolymer phase prepared in Example 8;
[0030] Figure 5 MIP cumulative porosity curves of slag-based magnesium phosphate geopolymers (7 days old) prepared in Example 11 and Comparative Example 17;
[0031] Figure 6This is a graph showing the proportion of pores of different sizes in the slag-based magnesium phosphate geopolymer (7 days old) MIP prepared in Example 11 and Comparative Example 17;
[0032] Figure 7 TG and DTG curves of the slag-based magnesium phosphate geopolymer at different ages prepared in Example 41;
[0033] Figure 8 FTIR spectra of the slag-based magnesium phosphate geopolymer at different ages prepared in Example 41;
[0034] Fig. 9 The XRD patterns of the slag-based magnesium phosphate geopolymers prepared in Examples 50 to 52 at 1 day of age;
[0035] Fig.10 These are the XRD spectra of the slag-based magnesium phosphate geopolymer prepared in Example 51 at different ages. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing a slag-based magnesium phosphate geopolymer without burning, comprising the following steps:
[0037] The geopolymer slurry is poured and vibrated to obtain a molded test block; the geopolymer slurry comprises, by weight, 10 to 50 parts of shield slag powder, 20 to 40 parts of dihydrogen phosphate, 40 to 90 parts of dead-burned magnesium oxide, 10 to 30 parts of water, 0 to 15 parts of borax, and 0 to 5 parts of an acid admixture;
[0038] The molded test blocks are hardened and cured in sequence to obtain a slag-based magnesium phosphate geopolymer; the hardening and curing temperatures are independently 20-25°C.
[0039] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0040] The invention pours the geopolymer slurry and then vibrates it to form a formed test block.
[0041] In parts by mass, the composition of the geopolymer slurry includes 10 to 50 parts of shield slag powder, preferably 15 to 45 parts, more preferably 20 to 40 parts, specifically preferably 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 or 50 parts.
[0042] In the present invention, the shield slag powder is dry shield slag powder, and the particle size of the shield slag powder is ≥40 mesh, more preferably ≥80 mesh, and further preferably ≥100 mesh.
[0043] In the present invention, the shield slag powder is preferably obtained by pre-treatment of shield slag, and the pre-treatment preferably includes first drying, crushing, second drying, pulverizing and screening in sequence. In the present invention, the first drying is preferably sun-drying, and the time of sun-drying is preferably 1 to 7 days, more preferably 3 to 7 days, and the purpose of sun-drying is to remove most of the water. The present invention has no special restrictions on the crushing, and the large pieces of shield slag are preliminarily crushed into small pieces of shield slag by a crushing method well known to those skilled in the art. In the present invention, the temperature of the second drying is preferably 40 to 80°C, more preferably 50 to 60°C; the present invention has no special restrictions on the time of the second drying, and it can be dried to constant weight; the second drying is preferably carried out in an oven. In the present invention, the size of the sieve for screening is preferably 40 to 100 meshes, more preferably 60 to 80 meshes, and the part under the sieve is shield slag powder. The present invention adopts the above-mentioned pretreatment method to pretreat the shield slag, which can ensure that the shield slag powder is in a completely dry state, and can remove large particles of shield slag, ensuring the uniformity and fineness of the shield slag powder. In the present invention, the shield slag is the shield slag residual mud obtained after sand separation treatment (sand screening).
[0044] Based on the mass fraction of the shield slag powder, the composition of the geopolymer slurry includes 20 to 40 parts of dihydrogen phosphate, preferably 25 to 35 parts, more preferably 30 parts, and specifically preferably 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts. In the present invention, the dihydrogen phosphate preferably includes potassium dihydrogen phosphate and / or ammonium dihydrogen phosphate; the dihydrogen phosphate is preferably an industrial grade raw material, and the purity is preferably ≥98%. In the present invention, the dihydrogen phosphate is preferably dried, ground and sieved in sequence before use, and the sieve portion is used; the drying temperature is preferably 40-80°C, more preferably 50-60°C; the drying time is preferably 24-48h, more preferably 24-30h; the sieve size is preferably 100 mesh; the particle size of the dihydrogen phosphate after sieving is preferably ≥100 mesh, more preferably 100-200 mesh, and further preferably 100-150 mesh.
[0045] Based on the mass percentage of the shield slag powder, the composition of the geopolymer slurry includes 40 to 90 parts of dead-burned magnesium oxide, preferably 45 to 85 parts, more preferably 50 to 80 parts, further preferably 55 to 75 parts, and specifically preferably 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56, 57, 58, 59, 50, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89 or 90 portions. In the present invention, the dead-burned magnesium oxide is preferably sieved before use, and the particle size of the dead-burned magnesium oxide after sieving is preferably ≥40 mesh, more preferably 40-200 mesh, and further preferably 50-100 mesh. In a specific embodiment, the average particle size of the dead-burned magnesium oxide is 7.24-11.11 μm; the content of the dead-burned magnesium oxide is preferably 86.6-92.8wt%, the calcination temperature is preferably 1600-1700°C, and the specific surface area is preferably 381.8-618.2m 2 / kg.
[0046] Calculated by mass proportion of the shield slag powder, the composition of the geopolymer slurry includes 10 to 30 parts of water, preferably 15 to 25 parts, more preferably 20 parts, specifically preferably 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.
[0047] Based on the mass fraction of the shield slag powder, the composition of the geopolymer slurry includes 0 to 15 parts of borax, preferably 1 to 12 parts, more preferably 5 to 10 parts, and specifically preferably 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 parts. In the present invention, the borax is preferably dried, ground and sieved in sequence before use, and the under-sieve part is used; the drying temperature is preferably 40 to 80°C, more preferably 50 to 60°C; the drying time is preferably 24 to 48h, more preferably 24 to 30h; the sieve size is preferably 40 mesh, more preferably 100 to 150 mesh; the particle size of the sieved dihydrogen phosphate is preferably ≥100 mesh, more preferably 100 to 200 mesh, and further preferably 100 to 150 mesh.
[0048] The composition of the geopolymer slurry includes 0 to 5 parts of acid admixture, preferably 1 to 4 parts, more preferably 2 to 3 parts, and specifically preferably 0 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, based on the mass fraction of the shield slag powder. In the present invention, the acid admixture preferably includes at least one of acetic acid, citric acid and oxalic acid, more preferably acetic acid.
[0049] In the present invention, the magnesium-phosphorus ratio of the geopolymer slurry (i.e., the mass ratio of dead-burned magnesium oxide / dihydrogen phosphate) is preferably 0.56-4, more preferably 0.93-2.84, and specifically preferably 0.93, 1, 1.3, 1.48, 1.89, 2, 2.5, 2.8 or 2.84; the water-cement ratio of the geopolymer slurry (i.e., the ratio of the mass of water to the total mass of shield slag powder, dead-burned magnesium oxide and dihydrogen phosphate) is preferably 0.14-0.18, more preferably 0.14-0.18, and specifically preferably 0.14, 0.16 or 0.18; the acid-magnesium ratio of the geopolymer slurry (i.e., the mass ratio of acid admixture / dead-burned magnesium oxide) is preferably 0-9.69%, more preferably 0-5.48%, and specifically preferably 0%, 1.85%, 4.39% or 5.48%.
[0050] In the present invention, the preparation method of the geopolymer slurry preferably includes the following steps: dry mixing shield slag powder, dihydrogen phosphate, dead burned magnesium oxide and borax, and sequentially slowly and rapidly mixing the obtained dry mixing with acid admixtures and water to obtain the geopolymer slurry. In the present invention, the dry mixing time is preferably 1 to 3 minutes, more preferably 1.5 to 2.5 minutes, and more preferably 2 minutes; the dry mixing is preferably carried out in a JJ-5 planetary cement mortar mixer. In the present invention, the slow stirring speed is preferably 135 to 145 r / min, more preferably 140 r / min; the slow stirring time is preferably 30 to 60 seconds, more preferably 35 to 55 seconds, and more preferably 40 to 50 seconds. In the present invention, the rapid stirring speed is preferably 278 to 295 r / min, more preferably 280 to 290 r / min; the rapid stirring time is 2 to 5 minutes, more preferably 2.5 to 4.5 minutes, and more preferably 3 to 4 minutes. In the present invention, the temperatures for dry mixing, slow stirring and fast stirring are preferably room temperature (20-25° C.).
[0051] In the present invention, the pouring is preferably performed by placing the geopolymer slurry in a mold and scraping it flat.
[0052] In the present invention, the vibration molding time is preferably 1 to 3 minutes, more preferably 2 minutes; the vibration molding temperature is preferably room temperature.
[0053] After obtaining the molded test block, the present invention sequentially hardens and cures the molded test block to obtain a slag-based magnesium phosphate geopolymer; the hardening and curing temperatures are independently 20-25°C.
[0054] In the present invention, the curing temperature is 20-25°C, preferably 20-24°C, and more preferably 20-22°C; the curing ambient humidity is preferably 50-95%, more preferably 70-95%, and further preferably 80-95%; the curing time is preferably 1-6h, more preferably 2-5h, and further preferably 3-4h; the curing is preferably carried out in a curing room or a constant temperature and humidity chamber.
[0055] In the present invention, demoulding is preferably performed first and then curing is performed; the curing temperature is 20-25°C, preferably 20-24°C, and more preferably 20-22°C; the environmental humidity of the curing is preferably 50-95%, more preferably 70-95%, and further preferably 80-95%; the total time (i.e., age) of the hardening and curing is preferably 1-28 days, and in specific embodiments, it can be 1 day, 2 days, 3 days, 4 days, 5 days, 6 days, 7 days, 8 days, 9 days, 10 days, 11 days, 12 days, 13 days, 14 days, 15 days, 16 days, 7 days, 8 days, 19 days, 20 days, 21 days, 22 days, 23 days, 24 days, 25 days, 26 days, 27 days or 28 days; the curing is preferably constant temperature and humidity curing; the curing is preferably carried out in a curing room or a constant temperature and humidity chamber.
[0056] The present invention provides a slag-based magnesium phosphate geopolymer prepared by the firing-free preparation method described in the above technical scheme.
[0057] The present invention also provides the use of the slag-based magnesium phosphate geopolymer described in the above technical solution as a building material.
[0058] In order to further illustrate the present invention, a slag-based magnesium phosphate geopolymer and its firing-free preparation method and application provided by the present invention are described in detail below in combination with embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0059] In the following embodiments, the pretreatment of shield slag is as follows: the newly taken out shield slag (shield slag residual mud obtained after sand and soil separation treatment) is placed in a natural environment for exposure and air drying to remove most of the moisture so that the slag is agglomerated into hard lumps for initial crushing, and then the large agglomerated slag is initially crushed into small lumps, placed in a 60°C oven and continuously heated until the weight is constant, ensuring that the slag blocks are completely dry, crushed, and passed through an 80-mesh sieve. The part under the sieve is shield slag powder.
[0060] Potassium dihydrogen phosphate is an industrial-grade raw material with a purity of not less than 98%. It should be dried in a drying oven at 60°C for 24 hours before use, ground, and passed through a 100-mesh sieve, and the portion under the sieve should be used.
[0061] There are two types of dead-burned magnesium oxide, both of which are industrial-grade raw materials. The first type of dead-burned magnesium oxide has a calcination temperature of 1600°C, a content of 86.6wt%, an average particle size of 7.24μm, and a specific surface area of 618.2m 2 / kg; the second type of heavy burned magnesium oxide was calcined at 1700°C, with a content of 92.8wt%, an average particle size of 11.11μm, and a specific surface area of 381.8m 2 / kg; dead-burned magnesium oxide was sieved through a 40-mesh sieve before use, and the part under the sieve was used.
[0062] Borax is an industrial-grade raw material with a content greater than 95wt%. It is dried in a drying oven at 60°C for 24 hours before use, ground, and passed through a 100-mesh sieve, and the portion under the sieve is used.
[0063] The water is tap water.
[0064] The acid admixture was analytically pure acetic acid.
[0065] Example 1
[0066] The shield slag powder, potassium dihydrogen phosphate, dead-burned magnesium oxide and borax were placed in a JJ-5 planetary cement mortar mixer and dry-mixed for 2 minutes, and then water was added, and the mixture was first slowly stirred at 140r / min for 30s, and then rapidly stirred at 285r / min for 150s to obtain a geopolymer slurry. In terms of mass fractions, the geopolymer slurry consists of: 10 parts of shield slag powder, 32 parts of potassium dihydrogen phosphate, 90 parts of dead-burned magnesium oxide, 14 parts of borax, and 18 parts of water.
[0067] The geopolymer slurry was placed in a 40 mm×40 mm×40 mm mold, scraped and leveled, and then vibrated for 1 minute to obtain a molded test block.
[0068] The molded test block was placed in a constant temperature and humidity chamber at a temperature of 20° C. and a humidity of 95% for hardening for 3 hours and then demolded. The demolded test block was continued to be placed in a constant temperature and humidity chamber at a temperature of 20° C. and a humidity of 95% for curing to ages of 1 d, 3 d, 7 d and 28 d, respectively, to obtain a slag-based magnesium phosphate geopolymer, wherein the age is the total time of hardening and curing.
[0069] Compressive strength test of slag-based magnesium phosphate geopolymer: 1d compressive strength was tested with a loading speed of 2.4kN / s. Three cubic specimens with a side length of 40mm were tested and the arithmetic mean was taken as the 1d compressive strength. The test results are shown in Table 1.
[0070] Examples 2 to 52 and Comparative Examples 1 to 18
[0071] The slag-based magnesium phosphate geopolymer was prepared according to the method of Example 1, and the only difference from Example 1 was that the composition and preparation conditions of the geopolymer slurry were different, as shown in Table 1. Among them, Examples 1 to 6, Examples 14 to 25, Examples 32 to 39, Examples 42 to 48, Comparative Examples 1 to 4, Comparative Examples 6 to 10 and Comparative Examples 14 to 15 used the first dead-burned magnesium oxide; the other Examples and Comparative Examples used the second dead-burned magnesium oxide.
[0072] Table 1 Composition (mass parts) and preparation conditions of geopolymer slurry in Examples and Comparative Examples
[0073]
[0074]
[0075] Table 2 Compressive strength test results at different ages
[0076]
[0077]
[0078] It can be seen from Examples 1 to 49 in Tables 1 to 2 that the slag-based magnesium phosphate geopolymer prepared by the present invention has low water consumption and can achieve high compressive strength after curing for 1 day, and its compressive strength will continue to increase with age, so it can be used as a building material.
[0079] The magnesium-phosphorus ratios of Comparative Examples 2 to 4 and Comparative Examples 6 to 10 in Table 1 are too low, so that the amount of dead-burned magnesium oxide in the slag-based magnesium phosphate geopolymer is insufficient to generate sufficient binder, while the excess amount of potassium dihydrogen phosphate may cause water absorption and expansion, thereby having a negative impact on the strength.
[0080] The water-cement ratios of Comparative Examples 1 to 4 and Comparative Example 10 in Table 1 are too high, which increases the porosity of the slag-based magnesium phosphate geopolymer, which not only reduces the density but also reduces the overall strength.
[0081] The acid-ash ratios of Comparative Examples 6 to 10 in Table 1 are too high, so that there are too many hydrogen ions in the slag-based magnesium phosphate geopolymer, which will lead to too fast crystal growth of the hydration product, poor crystal quality, and many defects, which is also unfavorable to the strength.
[0082] The present invention obtains a slag-based magnesium phosphate geopolymer with better mechanical properties by controlling the magnesium-phosphorus ratio, water-cement ratio and acid-cement ratio (the amount of each raw material used in the preparation).
[0083] Test Example 1
[0084] Analysis of the slag-based magnesium phosphate geopolymer prepared in Example 8
[0085] Combined with the TIMA comprehensive mineral analysis system, all element types and phase composition of slag-based magnesium phosphate geopolymers are obtained to characterize the microstructure of the geopolymers. Figure 1 This is the TIMA phase composition diagram of the slag-based magnesium phosphate geopolymer prepared in Example 8. It can be seen that in addition to the hydration products of potassium magnesium phosphate (KMgPO4·6H2O, Struvite-K, Newberyite) generated in the slag-based magnesium phosphate geopolymer, the active silicon and active aluminum components of the slag in the raw material are also stimulated and participate in the geopolymerization reaction to generate amorphous magnesium calcium silicate hydrates, which reduces the alkalinity of the system, reduces the maximum heat release rate of the system, improves the heat release of the system, and improves the comprehensive performance of the geopolymer in the present invention.
[0086] A scanning electron microscope is used to quickly obtain BSE images and X-ray energy spectrum data of the surface of slag-based magnesium phosphate geopolymer. With the help of modern graphics technology and computer data processing technology, the sample morphology and tens of millions of energy spectrum test points are statistically fitted. The mineral phase boundaries of different products in the geopolymer sample after coagulation are determined based on the differences in mineral composition reflected by BSE and energy spectrum. The energy spectrum components and spectra are compared with the information in the mineral database to confirm the type of mineral generated. The phase composition of the slag-based polymer and the content, particle size and distribution of minerals after coagulation, as well as the element occurrence state, are quickly and accurately determined.
[0087] Figure 2 The X-ray energy spectrum element distribution diagram of the slag-based magnesium phosphate geopolymer prepared in Example 8 shows that the active components of calcium and silicon in the slag are distributed around the magnesium oxide, and the distribution of phosphorus and potassium elements shows that there are a large number of hydration products of magnesium phosphate salts. Excess magnesium oxide is distributed in the entire phase. In addition to participating in the generation of magnesium potassium phosphate hydration products and other intermediates, it also acts as a fine aggregate as a structural filler to improve strength.
[0088] Figure 3 This is an enlarged view of the phase distribution area of the slag-based magnesium phosphate geopolymer prepared in Example 8. From the phase distribution map and the energy spectrum, it can be seen that there are two amorphous hydration products; Figure 4 The EDS energy spectrum and element quantitative statistical diagram of two amorphous hydration products of the slag-based magnesium phosphate geopolymer prepared in Example 8; the atomic ratio is obtained by combining the energy spectrum element analysis of the TIMA analysis system and the quantitative statistical analysis of the data of more than 20,000 scanning points in each phase region. Both hydration products come from the excited components of the slag (see Figure 4 ), one is a magnesium-rich silicate-phosphate composite indefinite form product represented by silicon, magnesium and phosphorus elements ( Figure 3Middle area 1). One is magnesium calcium silicate (amorphous hydroxyapatite) hydrate mainly composed of silicon and calcium elements ( Figure 3 These two types of hydrates are attached to the magnesium oxide raw material and the periphery of the magnesium potassium phosphate hydrate, playing a bridging role between the skeletons ( Figure 3 In the middle regions 2 and 4), the hydration products of each component cross-link with each other and synergistically improve the mechanical properties of the slag-based magnesium phosphate geopolymer.
[0089] Test Example 2
[0090] MIP analysis of the soil-based magnesium phosphate geopolymer (7 days old) prepared in Example 11 and Comparative Example 17
[0091] Figure 5 The MIP cumulative porosity curves of the slag-based magnesium phosphate geopolymer (7d age) prepared in Example 11 and Comparative Example 17 show that the cumulative porosity of the samples of Example 11 and Comparative Example 17 increases with the increase of pore size and the final cumulative porosity is similar. The porosity of the sample of Example 11 increases faster within the small pore size range, indicating that the sample of Example 11 may contain more small pores. It can be seen that the addition of a certain amount of slag can improve the pore structure of magnesium phosphate cement and convert more pore sizes into small pores, thereby improving the mechanical properties of the slag-based magnesium phosphate geopolymer.
[0092] Figure 6 The following is a graph showing the proportion of pores of different sizes in the slag-based magnesium phosphate geopolymer (7d age) prepared in Example 11 and Comparative Example 17. Comparison of the samples in Example 11 and Comparative Example 17 shows that after the addition of slag, the proportion of pores larger than 0.2 μm is significantly reduced compared with the samples without slag, and the changes are concentrated in the pore size range of 1 to 50 μm, while the proportion of pores smaller than 0.2 μm is significantly increased, indicating that the addition of a certain amount of slag converts a large number of pores in the pore size range of 1 to 50 μm in the magnesium phosphate cement into pores smaller than 0.2 μm, which significantly improves the pore structure and thus enhances the mechanical properties of the slag-based magnesium phosphate geopolymer.
[0093] Test Example 3
[0094] TG and DTG analysis of the slag-based magnesium phosphate geopolymer at different ages prepared in Example 41
[0095] Figure 7 The TG and DTG curves of the slag-based magnesium phosphate geopolymer at different ages prepared in Example 41 show that the hydration products mainly decompose at 50-160°C. As the age increases, the final weight loss of the sample also increases, and the position of the DTG peak moves slightly to the right, indicating that more hydration products are generated as the age increases, and more heat is required to make the hydration products lose their crystal water. It can be seen that the generation of more hydration products can improve the mechanical properties of magnesium phosphate cement.
[0096] Test Example 4
[0097] FTIR spectral analysis of the slag-based magnesium phosphate geopolymer at different ages prepared in Example 41.
[0098] Figure 8 The FTIR spectra of the slag-based magnesium phosphate geopolymer prepared in Example 41 at different ages show that as the age increases, the OH stretching vibration (3434 cm -1 2935cm -1 2366cm -1 ) and HOH bending vibration (1610cm -1 1434cm -1 The peak intensity of the spectral region at ( ) increases, indicating that the bound water in the reaction product increases. 3- The ν3 signal is at 1110 cm -1 The concentration of KH2PO4 gradually weakened and almost disappeared with the age, indicating that the unreacted KH2PO4 continued to be consumed and converted into hydration products with the increase of age. 3- The stretching vibration of ν3 (1010cm -1 ), PO4 3- The bending vibration of ν4 (571cm -1 ) and 767cm -1 PO4 3- The peak intensity of the spectral region also increases with age, indicating that more hydration products are generated, which is consistent with the results of TG and DTG analysis. The generation of more hydration products improves the mechanical properties of magnesium phosphate cement.
[0099] Test Example 5
[0100] X-ray diffraction (XRD) pattern analysis of the slag-based magnesium phosphate geopolymers at different ages prepared in Examples 50 to 52.
[0101] Fig. 9 This is the XRD spectrum of the slag-based magnesium phosphate geopolymer prepared in Examples 50 to 52 at the age of 1 day. Fig.10 These are the XRD spectra of the slag-based magnesium phosphate geopolymer prepared in Example 51 at different ages.
[0102] from Fig. 9It can be seen from the X-ray diffraction (XRD) patterns that the crystal phases of Examples 50 to 52 have changed significantly with the increase in the amount of slag added, especially the diffraction peaks of struvite-K, MgO and SiO2 have shown a clear trend of change. With the increase in the amount of slag added, the relative intensity of the peak of the MgO raw material gradually decreases, and the characteristic peaks of struvite-K at 2θ angles of about 20°, 30° and 50° gradually increase, indicating that the addition of slag improves the crystallinity and content of the hydration products of the magnesium potassium phosphate-based polymer, and is improved with the increase in the amount of slag added, thereby making a significant contribution to the overall strength of the material. Especially in Fig.10 In the example 51, the diffraction peak intensity of struvite-K gradually increased from 1 day to 28 days, indicating the further maturation of the crystal phase and the optimization of the crystal structure. In addition, the diffraction peaks of MgO and SiO2 also changed to a certain extent at each time point. Therefore, the crystal phase evolution process of the slag-based magnesium potassium phosphate geopolymer has been significantly enhanced, which improves the strength of the material.
[0103] In summary, the TIMA comprehensive mineral analysis system clearly analyzes the composition of each phase of geopolymers and reveals the distribution characteristics of each element in the material. MIP analysis shows that the addition of slag improves the pore structure of magnesium phosphate cement. The TG and DTG, FTIR, and XRD spectral analyses of each age mutually prove that with the increase of age, more hydration products are generated in slag-based magnesium phosphate geopolymers, verifying the reaction mechanism and structural optimization path of slag-based magnesium phosphate geopolymers at the microscopic level. This provides strong evidence for the present invention in improving material properties, especially mechanical properties, and also lays a foundation for the future development of higher performance green building materials.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a slag-based magnesium phosphate geopolymer without burning, comprising the following steps: The geopolymer slurry is poured and vibrated to obtain a molded test block; The geopolymer slurry comprises, by weight, 10 to 50 parts of shield slag powder, 20 to 40 parts of dihydrogen phosphate, 40 to 90 parts of dead-burned magnesium oxide, 10 to 30 parts of water, 0 to 15 parts of borax, and 0 to 5 parts of acid admixture; The molded test blocks are hardened and cured in sequence to obtain a slag-based magnesium phosphate geopolymer; the hardening and curing temperatures are independently 20-25°C.
2. The firing-free preparation method according to claim 1, characterized in that: The particle sizes of the shield slag powder and the dead-burned magnesium oxide are independently ≥40 meshes.
3. The firing-free preparation method according to claim 1, characterized in that: The dihydrogen phosphate includes potassium dihydrogen phosphate and / or ammonium dihydrogen phosphate; The particle size of the dihydrogen phosphate is ≥100 mesh.
4. The firing-free preparation method according to claim 1, characterized in that: The particle size of the dead-burned magnesium oxide is ≥40 meshes.
5. The firing-free preparation method according to claim 1, characterized in that: The acid additive includes at least one of acetic acid, citric acid and oxalic acid.
6. The calcination-free preparation method according to any one of claims 1 to 5, characterized in that: The preparation method of the geopolymer slurry comprises the following steps: dry-mixing shield slag powder, dihydrogen phosphate, dead-burned magnesium oxide and borax, and sequentially slowly and rapidly mixing the dry-mixed powder with an acid additive and water to obtain the geopolymer slurry; The dry mixing time is 1 to 3 minutes; The slow stirring speed is 135-145 r / min, and the time is 30-60 s; The rapid stirring speed is 275-295 r / min, and the time is 2-5 min.
7. The firing-free preparation method according to claim 1, characterized in that: The vibration molding time is 1 to 3 minutes.
8. The firing-free preparation method according to claim 1, characterized in that: The environmental humidity of the hardening and curing is independently 50-95%; the hardening time is 1-6 hours; The total time of hardening and curing is 1 to 28 days.
9. The slag-based magnesium phosphate geopolymer obtained by the firing-free preparation method according to any one of claims 1 to 8.
10. Use of the slag-based magnesium phosphate geopolymer according to claim 9 as a building material.